Revisit western theories in the professionalization process of teaching occupation in South-Asia - Quddus, S. M. Abdul (2011)
This is a theoretical paper based on review of theories on the sociology of professions. This study analyses the contributions of western scholars over the years in the area of professionalization of occupations. The paper argues that main western ‘traditions’ in the sociology of professions have narrowly mapped the conceptions ‘profession’ and ‘professionalization’ of occupations. Our point of departure is that such a narrow conceptualization makes the concepts problematic, especially when used in the context of developing societies in South Asia. This paper draws the conclusion that the concepts of profession and professionalization need to be oriented towards wider socio-economic, political contexts and the ‘global movements’ both in the West and the East.